2012
DOI: 10.4088/jcp.11m07607
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressive Treatment With Monoamine Oxidase Inhibitors and the Occurrence of Intraoperative Hemodynamic Events

Abstract: Severe adverse hemodynamic events, such as hypertension and tachycardia, did not occur more frequently in users of both the irreversible MAOI tranylcypromine and the reversible MAO-A inhibitor moclobemide compared to nonusers. These findings suggest that there is no longer much justification to discontinue these MAOIs before surgery, with the considerable risk of compromising patients' psychiatric status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…3 Discontinuation of MAO inhibitors for regional anesthesia is not essential as also discussed for general anesthesia. 12,17,18 However, the risk should be higher in patients who are being treated with MAO inhibitors despite contraindications. Moreover, it has been proved that increased psychiatric risk in a patient treated with MAO inhibitors outweighs the increased perioperative risk from continuing treatment during noncardiac surgery.…”
Section: Resultsmentioning
confidence: 99%
“…3 Discontinuation of MAO inhibitors for regional anesthesia is not essential as also discussed for general anesthesia. 12,17,18 However, the risk should be higher in patients who are being treated with MAO inhibitors despite contraindications. Moreover, it has been proved that increased psychiatric risk in a patient treated with MAO inhibitors outweighs the increased perioperative risk from continuing treatment during noncardiac surgery.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of a new generation of reversible MAO inhibitors appears to avoid this adverse effect. In fact, a very recent retrospective analysis reported that severe adverse hemodynamic events, such as hypertension and tachycardia, do not occur more frequently in users of both the irreversible MAO inhibitor tranylcypromine and the reversible MAO-A inhibitor moclobemide compared to nonusers [119]. In this investigation, cardiac contractility was not included as an endpoint.…”
Section: Discussionmentioning
confidence: 98%
“…Es existieren aber auch Berichte über unkomplizierte Verläufe von operativen Eingriffen unter Narkose bei gleichzeitiger Fortsetzung einer Einnahme von MAO-Inhibitoren [102,103].…”
Section: Wechselwirkungen Zwischen Tranylcypromin Und Etomidatunclassified